plzzzz solve this question urgently .
Attachments:
![](https://hi-static.z-dn.net/files/d0e/3570ed650d286e9bbc6d6a1b9d1f8252.jpg)
Answers
Answered by
2
Sol : ( 1 / 4 )^(-2 ) - 3 x 8^0 - ( 1 / 64 )^ ( - 1 / 2 )
Using identity , { ( 1 / a )^( - m ) = a^m }
= ( 4 )² - 3 x 8^0 - ( 64 )^( 1 /2 )
Using identity { a^0 = 1 }
= 16 - 3 x 1 - ( 64 )^(1/2 )
Using identity , { a^( 1 / 2 ) = √a }
= 16 - 3 - √64
= 16 - 3 - 8
= 16 - 11
= 5.
__________________________________________________________
Using identity , { ( 1 / a )^( - m ) = a^m }
= ( 4 )² - 3 x 8^0 - ( 64 )^( 1 /2 )
Using identity { a^0 = 1 }
= 16 - 3 x 1 - ( 64 )^(1/2 )
Using identity , { a^( 1 / 2 ) = √a }
= 16 - 3 - √64
= 16 - 3 - 8
= 16 - 11
= 5.
__________________________________________________________
Anonymous:
Will you mark it as brainliest ?
Answered by
2
..........answer = 5
Attachments:
![](https://hi-static.z-dn.net/files/dde/438db9e3cafa6e71de43d35a8718404b.jpg)
Similar questions